1999
DOI: 10.1007/s002770050474
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of apoptosis and proliferation in idiopathic (primary) myelofibrosis

Abstract: A retrospective study of 120 patients with the clinically and histologically established diagnosis of idiopathic (primary) myelofibrosis (IMF) was performed to determine prognostic factors of predictive value, including parameters characterizing the dynamics of hematopoietic cell kinetics. In contrast to previous studies, our cohort comprised the full spectrum of the disease, from initial prefibrotic to advanced osteosclerotic stages. The in situ end-labeling (ISEL) technique was used to demonstrate apoptosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…This caspase is commonly defined as effector caspase (Migliarini et al 2005). Evaluation of both precursor cell proliferation and apoptosis rate is applied in hematological studies to evaluate the rate of cell turnover and hematopoietic activity (Thiele et al 1997; Kvasnicka et al 1999). The presence of PCNA in fish hematopoietic tissue was confirmed by Leung et al (2005) for Danio rerio .…”
Section: Introductionmentioning
confidence: 99%
“…This caspase is commonly defined as effector caspase (Migliarini et al 2005). Evaluation of both precursor cell proliferation and apoptosis rate is applied in hematological studies to evaluate the rate of cell turnover and hematopoietic activity (Thiele et al 1997; Kvasnicka et al 1999). The presence of PCNA in fish hematopoietic tissue was confirmed by Leung et al (2005) for Danio rerio .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, risk classification of MPDs is mainly based on clinical data [5][6][7][8][9][10][11] and only a few clinical trials include explicitly BM biopsy examinations. 2,[12][13][14] Especially in those disorders associated with an elevated platelet count, differentiation between essential thrombocythemia (ET) and allied subtypes may be difficult without the possibility to recognize characteristic in relation with corresponding clinical data. 3 Regarding prognostic calculations in these cases, a most serious impairment is created by the failure to consider survival mortalities resulting from other causes than the underlying disorder, because in most studies only absolute (observed) survival rates have been calculated.…”
mentioning
confidence: 99%
“…In univariate analysis, the prodromal phases show a more favorable survival in comparison with more advanced stages (MMM). However, in multivariate calculations, evolution of BM fibrosis displayed no significant influence on survival [84][85][86] .…”
Section: Chronic Idiopathic Myelofibrosismentioning
confidence: 99%
“…Furthermore, it is important that in BM specimens maturation defects should be recognized in at least two lineages [82] , especially erythropoiesis and megakaryocytes (atypical micromegakaryocytes, abnormal nuclear lobulation, compact nuclei) [83] . Finally, although in the past decade many groups were engaged in the study of risk stratification and prognosis of CIMF patients, a comparison of these data reveals an extreme heterogeneity [84,85] . This result may be significantly influenced by including patients with PPMM into the corresponding calculations and the failure to recognize the prefibrotic and early stages of this disorder [58,85] .…”
Section: Chronic Idiopathic Myelofibrosismentioning
confidence: 99%